2016
DOI: 10.1016/j.jviromet.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Droplet digital PCR: A novel method for detection of influenza virus defective interfering particles

Abstract: Defective interfering (DI) particles are viruses that carry one or more large, internal deletions in the viral genome. These deletions occur commonly in RNA viruses due to polymerase error and yield incomplete genomes that typically lack essential coding regions. The presence of DI particles in a virus population can have a major impact on the efficiency of viral growth and is an important variable to consider in interpreting experimental results. Herein, we sought to develop a robust methodology for the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
(48 reference statements)
3
16
0
Order By: Relevance
“…For NL09-based viruses, 293T cells transfected with reverse genetics plasmids 16–24 h prior were co-cultured with MDCK cells at 37°C for 40–48 h. Supernatants were then propagated in MDCK cells from low MOI to generate NL09 working stocks. Defective interfering segment content of PB2, PB1, and PA segments was confirmed to be minimal for each virus stock, as described previously 68 ( Supplementary Figure 7 ). All plaque assays were performed in MDCK cells; viruses were also titered by flow cytometry and/or RT qPCR-based methods where indicated.…”
Section: Methodssupporting
confidence: 80%
“…For NL09-based viruses, 293T cells transfected with reverse genetics plasmids 16–24 h prior were co-cultured with MDCK cells at 37°C for 40–48 h. Supernatants were then propagated in MDCK cells from low MOI to generate NL09 working stocks. Defective interfering segment content of PB2, PB1, and PA segments was confirmed to be minimal for each virus stock, as described previously 68 ( Supplementary Figure 7 ). All plaque assays were performed in MDCK cells; viruses were also titered by flow cytometry and/or RT qPCR-based methods where indicated.…”
Section: Methodssupporting
confidence: 80%
“…Three biological replicates were tested for each virus stock. Based on the Ct values obtained with terminal and internal assays, relative differences in the amount of defective RNAs between 95/95(DVG-high) and 95/95(DVG-low) were evaluated as previously described [32]. Briefly, a ratio 2 (-CtT) :2 (-CtI) was calculated and compared for both virus stocks.…”
Section: Analysis Of Amount Of Defective Segmentsmentioning
confidence: 99%
“…Several studies have demonstrated the efficient dPCR platform searching different viruses [20][21][22][23][24][25]. Moreover, rapid, accurate and affordable molecular technology can be predictable with particular emphasis on emerging techniques (next generation sequencing, digital PCR, point of care testing and syndromic diagnosis) to simplify viral diagnosis in the next future [24,25]. Finally, the present findings show that dPCR enables direct and accurate detection of CCoV genome with efficiency and quantitative linearity both from fecal samples and infected cell suspensions.…”
Section: Resultsmentioning
confidence: 99%